2014
DOI: 10.1155/2014/408073
|View full text |Cite
|
Sign up to set email alerts
|

Higher Effective Oronasal versus Nasal Continuous Positive Airway Pressure in Obstructive Sleep Apnea: Effect of Mandibular Stabilization

Abstract: In subjects with OSA with higher oronasal than nasal Peff, this is partially explained by posterior mandibular displacement caused by the oronasal mask. Combination treatment with oronasal mask and MAD may be useful in some individuals if a nasal mask is not tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…One postulated mechanism is that pressure delivered through the mouth pushes the tongue and soft tissues backwards, resulting in upper airway obstruction . Alternatively, the force of the oronasal mask against the mandible may push the jaw backwards, resulting in more upper airway obstruction . Movement of the soft palate in a flagging motion with the use of oronasal masks, resulting in upper airway turbulence, has also been postulated to contribute to reduced efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…One postulated mechanism is that pressure delivered through the mouth pushes the tongue and soft tissues backwards, resulting in upper airway obstruction . Alternatively, the force of the oronasal mask against the mandible may push the jaw backwards, resulting in more upper airway obstruction . Movement of the soft palate in a flagging motion with the use of oronasal masks, resulting in upper airway turbulence, has also been postulated to contribute to reduced efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that there are specific aspects that predispose them to higher pressure requirements while using an oronasal mask. Kaminska et al () have shown that posterior mandibular displacement partially contributes to this phenomenon in these individuals through application of a mandibular advancement device to stabilise the jaw. This work is further supported by a recent experimental study by Andrade et al (), where they demonstrate decreases to either the retroglossal or retropalatal area with use of an oronasal mask.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, in a small study of six subjects, Kaminska et al showed that adding a mandibular advancement splint to CPAP with an oronasal mask enabled the CPAP requirement to be significantly lowered in three of the subjects. 8 Furthermore, mouth opening is an inherent feature of oronasal mask use, and mouth opening has previously been demonstrated to increase upper airway collapsibility. 23 Another possible explanation is that breathing through the mouth with an oronasal mask leads to the soft palate being pushed posteriorly, which may counteract the opening forces of nasal airflow and lead to a narrower airway than seen when using a nasal mask.…”
Section: Discussionmentioning
confidence: 99%
“…The CPAP level required to treat OSA varies between individuals. It has been reported that selected patients require higher CPAP levels with oronasal masks compared to nasal masks 8 ; however, the literature on whether CPAP requirements differ according to mask type is conflicting. A Cochrane review in 2006 concluded that due to an inadequate number of studies addressing the issue, the optimal CPAP interface was unclear.…”
Section: Introductionmentioning
confidence: 99%